THE ROLE OF GOOD FAITH IN COMMERCIAL TRANSACTIONS: A NORMATIVE ANALYSIS OF ITS INTERPRETATION AND ENFORCEMENT IN INDONESIAN BUSINESS LAW - Na'afi , Septiana; Putra, Irman (Gapenas Publisher, 2025)
This study analyzes the role of good faith (itikad baik) in commercial transactions within the framework of Indonesian business law using a normative juridical approach. Good faith, as a fundamental principle of contract law, is recognized in the Indonesian Civil Code (KUHPerdata), particularly Articles 1338 and 1339, which emphasize that contracts must be executed in good faith and in line with propriety. Despite its doctrinal importance, the interpretation and enforcement of good faith in Indonesia remain inconsistent. Judicial practice shows variations between a subjective approach—focusing on honesty of intention—and an objective approach—emphasizing fairness, reasonableness, and protection of counterpart interests. This inconsistency creates legal uncertainty and weakens business confidence. Comparative analysis with German, Dutch, and international frameworks such as the UNIDROIT Principles and CISG highlights the importance of codifying and applying good faith uniformly to promote fairness and predictability. The findings recommend clearer legislative guidelines, the adoption of objective standards, judicial consistency, and alignment with international practices to strengthen contractual stability and Indonesia’s competitiveness in global trade.